Spontaneous Regeneration of Plantlets Derived from Hairy Root Cultures of Lopezia racemosa and the Cytotoxic Activity of Their Organic Extracts - Norely Vargas-Morales; Norma Elizabeth Moreno-Anzúrez; Janeth Téllez-Román; Irene Perea-Arango; Susana Valencia-Díaz; Alfonso Leija-Salas; Edgar R. Díaz-García; Pilar Nicasio-Torres; María Del Carmen Gutiérrez-Villafuerte; Jaime Tortoriello-García; Jesús Arellano-García (Plants, 2022)
A histological analysis was performed with the aim of elucidating the spontaneous regeneration process of the hairy root lines LRT 2.3 and LRT 6.4, derived from Lopezia racemosa leaf explants and genetically transformed with the Agrobacterium rhizogenes strain ATCC15834/pTDT. The analysis showed both lines regenerate via indirect somatic embryogenesis; LRT 6.4 also regenerated by direct organogenesis. The morphogenic characteristics of the regenerated plantlets from both lines showed the typical characteristics, described previously, including a higher number of axillary shoot formation, short internodes, and plagiotropic roots compared with wild-type seedlings. The regeneration process occurred without the addition of plant growth regulators and was linked to the sucrose concentration in the culture medium. Reducing the sucrose concentration from 3% to 2%, 1%, and 0.5% increased the regeneration rate in LRT 6.4; the effect was less pronounced in LRT 2.3. The cytotoxic activity of different organic extracts obtained from roots and shoots were evaluated in the cancer cell lines HeLa (cervical carcinoma), HCT-15 (colon adenocarcinoma), and OVCAR (ovary carcinoma). The hexane and dichloromethane extracts from roots of both lines showed cytotoxic activity against the HeLa cell line. Only the dichloromethane extract from the roots of PLRT 2.3 showed cytotoxic activity against the OVCAR cell line. None of the methanol extracts showed cytotoxic activity, nor the shoot extracts from any solvent.